SIMVASTATIN GENERIK - DAP. Rasmika Dewi; DG. Diah Dharma Santhi; DM Sukrama; AA. Raka Karsana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
This study aims to know and determine the lipid profile in patients with hyperlipidemia who consumed Generic Simvastatin comparedwith its patent product contained in the Formularium at Sanglah Hospital. The observations made, were the measurement of the totalcholesterol and low-density lipoprotein (LDL) before and after the drug administration. A total of 30 subjects who met the inclusioncriteria, were divided into two (2) groups, each group consist of 15 persons, the first group was given 20 mg generic Simvastatin(1 tablet daily) for 15 days and Group II given 20 mg patent Simvastatin (1 tablet daily) for 15 day. After 15 days, their blood sampleswere taken and examined for total cholesterol and LDL. Once the data were collected, statistical analysis was done by using the normalitytest, homogeneity and t. Statistical analysis using p-value less than or equal to 0.05 was the limit of significance. The statistical analysisshowed that the data was normally distributed and homogeneous (p≥0.05). The T-test showed that there were significant differencesin the levels of total cholesterol and LDL serum samples before and after the administration of generic simvastatin and patents the(sig.=0.000). However, there was no significant difference in decreased levels of totall cholesterol samples between the generic Simvastatinand patent (sig=0.365 with α=0.05 level). Besides this, there was also no significant difference in the decreased levels of LDL betweengeneric Simvastatin and the patent one (sig=0.372 with α=0.05 level).